2017
DOI: 10.1089/thy.2017.0078
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Iodine Intake and Thyrotropin Reference Interval: Data from the Korean National Health and Nutrition Examination Survey

Abstract: This first nationwide survey demonstrates more than adequate iodine intake and a right-shifted distribution of serum TSH levels in the Korean general population. Nutritional iodine status is important for determining serum TSH levels and is associated with a high prevalence of hypothyroidism. Nutritional iodine status might need to be considered when establishing TSH reference intervals of populations in iodine-replete areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Epidemiological studies also found that the resident's average serum TSH level has risen due to the effects of increased iodine intake ( 25 ). A similar epidemiological survey reported by Korea showed that there was high iodine intake in Korea, resulting in serum TSH exhibiting a right-shifted distribution in that population ( 26 ).…”
Section: Discussionmentioning
confidence: 63%
“…Epidemiological studies also found that the resident's average serum TSH level has risen due to the effects of increased iodine intake ( 25 ). A similar epidemiological survey reported by Korea showed that there was high iodine intake in Korea, resulting in serum TSH exhibiting a right-shifted distribution in that population ( 26 ).…”
Section: Discussionmentioning
confidence: 63%
“…For example, TSH secretion has obvious circadian rhythm, with excessive secretion at night and lower in the morning [23]. Concurrently, iodine intake [24] and estrogen [25] are also shown to affect serum TSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Major food constituents with side-effects are iodine, fibers, and sodium (in seasoned laver). Iodine has beneficial effects on thyroid gland functioning, but excessive intake should be avoided to prevent potential adverse effects such as autoimmune thyroiditis or hypothyroidism [94][95][96][97][98]. Overconsumption of fibers can lead to vomiting or abdominal pain with diarrhea in people with sensitive stomachs and may cause dyspepsia even in healthy people due to generation of gases in the digestive system [99].…”
Section: Control Of Chemical Risksmentioning
confidence: 99%